Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the matrix equation for [tex]\( x \)[/tex] and [tex]\( y \)[/tex], follow these steps:
The given matrix equation is:
[tex]\[ \frac{1}{2} \left[\begin{array}{cc} 4 & 8 \\ x+3 & -4 \end{array}\right] - 3 \left[\begin{array}{cc} 1 & y+1 \\ -1 & -2 \end{array}\right] = \left[\begin{array}{cc} -1 & -5 \\ 7 & 4 \end{array}\right] \][/tex]
First, simplify the left side of the equation.
Calculate the scaled matrices:
[tex]\[ \frac{1}{2} \left[\begin{array}{cc} 4 & 8 \\ x+3 & -4 \end{array}\right] = \left[\begin{array}{cc} \frac{4}{2} & \frac{8}{2} \\ \frac{x+3}{2} & \frac{-4}{2} \end{array}\right] = \left[\begin{array}{cc} 2 & 4 \\ \frac{x+3}{2} & -2 \end{array}\right] \][/tex]
[tex]\[ 3 \left[\begin{array}{cc} 1 & y+1 \\ -1 & -2 \end{array}\right] = \left[\begin{array}{cc} 3 \cdot 1 & 3(y+1) \\ 3(-1) & 3(-2) \end{array}\right] = \left[\begin{array}{cc} 3 & 3y+3 \\ -3 & -6 \end{array}\right] \][/tex]
Now, subtract the two matrices:
[tex]\[ \left[\begin{array}{cc} 2 & 4 \\ \frac{x+3}{2} & -2 \end{array}\right] - \left[\begin{array}{cc} 3 & 3y+3 \\ -3 & -6 \end{array}\right] = \left[\begin{array}{cc} 2 - 3 & 4 - (3y + 3) \\ \frac{x+3}{2} + 3 & -2 - (-6) \end{array}\right] = \left[\begin{array}{cc} -1 & 1 - 3y \\ \frac{x+3}{2} + 3 & 4 \end{array}\right] \][/tex]
Set this result equal to the given matrix:
[tex]\[ \left[\begin{array}{cc} -1 & 1 - 3y \\ \frac{x+3}{2} + 3 & 4 \end{array}\right] = \left[\begin{array}{cc} -1 & -5 \\ 7 & 4 \end{array}\right] \][/tex]
Now, match the corresponding elements:
1. Top-left:
[tex]\[ -1 = -1 \][/tex]
This is true, so it is correct.
2. Top-right:
[tex]\[ 1 - 3y = -5 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 1 - 3y = -5 \\ 1 + 5 = 3y \\ 6 = 3y \\ y = 2 \][/tex]
3. Bottom-left:
[tex]\[ \frac{x+3}{2} + 3 = 7 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ \frac{x+3}{2} + 3 = 7 \\ \frac{x+3}{2} = 4 \\ x + 3 = 8 \\ x = 5 \][/tex]
4. Bottom-right:
[tex]\[ 4 = 4 \][/tex]
This is true, so it is correct.
Therefore, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are:
[tex]\[ \boxed{x = 5, y = 2} \][/tex]
The given matrix equation is:
[tex]\[ \frac{1}{2} \left[\begin{array}{cc} 4 & 8 \\ x+3 & -4 \end{array}\right] - 3 \left[\begin{array}{cc} 1 & y+1 \\ -1 & -2 \end{array}\right] = \left[\begin{array}{cc} -1 & -5 \\ 7 & 4 \end{array}\right] \][/tex]
First, simplify the left side of the equation.
Calculate the scaled matrices:
[tex]\[ \frac{1}{2} \left[\begin{array}{cc} 4 & 8 \\ x+3 & -4 \end{array}\right] = \left[\begin{array}{cc} \frac{4}{2} & \frac{8}{2} \\ \frac{x+3}{2} & \frac{-4}{2} \end{array}\right] = \left[\begin{array}{cc} 2 & 4 \\ \frac{x+3}{2} & -2 \end{array}\right] \][/tex]
[tex]\[ 3 \left[\begin{array}{cc} 1 & y+1 \\ -1 & -2 \end{array}\right] = \left[\begin{array}{cc} 3 \cdot 1 & 3(y+1) \\ 3(-1) & 3(-2) \end{array}\right] = \left[\begin{array}{cc} 3 & 3y+3 \\ -3 & -6 \end{array}\right] \][/tex]
Now, subtract the two matrices:
[tex]\[ \left[\begin{array}{cc} 2 & 4 \\ \frac{x+3}{2} & -2 \end{array}\right] - \left[\begin{array}{cc} 3 & 3y+3 \\ -3 & -6 \end{array}\right] = \left[\begin{array}{cc} 2 - 3 & 4 - (3y + 3) \\ \frac{x+3}{2} + 3 & -2 - (-6) \end{array}\right] = \left[\begin{array}{cc} -1 & 1 - 3y \\ \frac{x+3}{2} + 3 & 4 \end{array}\right] \][/tex]
Set this result equal to the given matrix:
[tex]\[ \left[\begin{array}{cc} -1 & 1 - 3y \\ \frac{x+3}{2} + 3 & 4 \end{array}\right] = \left[\begin{array}{cc} -1 & -5 \\ 7 & 4 \end{array}\right] \][/tex]
Now, match the corresponding elements:
1. Top-left:
[tex]\[ -1 = -1 \][/tex]
This is true, so it is correct.
2. Top-right:
[tex]\[ 1 - 3y = -5 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 1 - 3y = -5 \\ 1 + 5 = 3y \\ 6 = 3y \\ y = 2 \][/tex]
3. Bottom-left:
[tex]\[ \frac{x+3}{2} + 3 = 7 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ \frac{x+3}{2} + 3 = 7 \\ \frac{x+3}{2} = 4 \\ x + 3 = 8 \\ x = 5 \][/tex]
4. Bottom-right:
[tex]\[ 4 = 4 \][/tex]
This is true, so it is correct.
Therefore, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are:
[tex]\[ \boxed{x = 5, y = 2} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.